KINERJA ARRESTER AKIBAT INDUKSI SAMBARAN PETIR - Syakur, Abdul; Warsito, Agung (Transmisi, 2009)
Electricity demand continues to increase so that the required power in a large number of high quality and reliability. Problems in electric power system that occur in transmission and distribution lines that is often of lightning stroke. This is because Indonesia is in the region the equator with a tropical climate and high humidity, so that Indonesia has a number of lightning strikes.In this paper the lightning stroke and lightning arrester performance on distribution lines 20 kV were simulated using EMTP (Electromagnetic Transient Program) for lightning stroke observation.As case study, Mojosongo 1 main feeder 20 kV three phase lines were used. From simulation of lightning stroke 20 kA in By1-61-61E-84-9IÂ  on S phase at 0,1 ms, will experience of increase of voltage on S phase was 1,3054 MV and for R phase and T phase will experience of increase of induced voltage were 0,79539 MV and 0,80484 MV. Then we will see performance of MOV Arrester (Metal Oxide Varistor) in overcoming lightning stroke trouble, where arrester can decrease voltage up to 15,198 kV on S phase, while at R phase and T phase arrester can decrease voltage up to 11,375 kV and 13,616 kV.Â Keywords: Distribution lines 20 kV, lightning arrester, lightning stroke.